Improvement of the vehicle warm-up performance through low thermal inertia exhaust heat recovery unit / Azmi Osman - Azmi, Osman (2021)
Internal combustion engines in general waste plenty of heat to the exhaust gas and coolant for every milligram of fuel burned. Considering that daily driving consists of frequent cold start, idling and part load driving within short driving distances, the potentials to recover heat from high enthalpy exhaust gas are limited to hard acceleration, hill climbing and highway driving. These constraints limit many heat recovery technologies that rely on conversion of thermal energy into electricity or kinetic energy. In recovering precious energy from the low enthalpy exhaust gas early and sustainably, a low thermal inertia exhaust heat recovery unit (EHRU) is proposed to be integrated to the simplified split cooling circuit used in the earlier studies to expedite the powertrain warm-up. This lightweight, compact and simple EHRU concept made of machined steel plate is targeted for naturally aspirated engines that are still being widely used in motorcycles, stationary engines and small car segments worldwide. Large temperature difference between the coolant and exhaust gas was possible using cooler coolant feed from the bottom of the cylinder blockï¿½s water jacket rear end. To prove its effectiveness in speeding up the recovered heat availability for reuse, a 1.3l passenger car equipped with strategically placed multiple thermocouples and flow meters was tested using idle and NEDC tests. The EHRU was later modeled using a simplified energy system (SES) to overcome the experimental limitations. From the experiments and classical analysis, the recovered thermal energy was available in just 23-25 seconds instead of 50 seconds after cold start. The improvements over the variant with no EHRU revealed during the idle and NEDC tests are in the range of 0.9-13.9% and 1.6-25.1% respectively. The study also provided a new direction in the design of EHRU and its integration into an engine.